The Effects of Training and Mentoring on Farmers’ Compliance with RSPO-Based Good Oil Palm Plantation Practices - Miftah Ainul Utami; Delyana R Pulungan (Social Science Academic, 2026)
Members of the Tani Mandiri Farmers’ Group (Gapoktan) in LautTador Subdistrict, Batu Bara Regency, have received training and mentoring to maintain their Roundtable on Sustainable Palm Oil (RSPO) certification; however, several internal audit findings still indicate gaps in the implementation of best practices in the field. This study aims to examine the relationship between training and mentoring and farmers’ compliance scores with RSPO-based best practices in oil palm plantations, both individually and in combination. The research design was an explanatory survey of 79 farmers selected using proportionate stratified random sampling from among 377 certified members across five farmer groups. Data were collected via a Likert-scale questionnaire that had been tested for validity and reliability, and then analyzed using multiple linear regression. The initial model yielded the equation Y = 4.545 + 0.936X1 + 0.270X2, with training (Beta = 0.573) and mentoring (Beta = 0.241) both showing positive and significant relationships with compliance scores (p < 0.01), and explaining 47.7% of the variance (F = 34.641; p < 0.001). Since the classical Glejser test indicated heteroscedasticity, these coefficients still need to be further confirmed using robust standard errors. These preliminary findings suggest that strengthening technical training and providing more regular on-site mentoring have the potential to support consistent compliance, although the cross-sectional design of this study cannot yet establish a causal relationship.